Pengaruh Komitmen dan Sertifikasi terhadap Kesejahteraan dan Implikasinya pada Kinerja Guru Sekolah Dasar Negeri di Kelurahan Penyengat Rendah Kota Jambi - Dewita Afrianti; Arna Suryani; Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2023)
Each individual has a commitment to themselves to be personally and individually responsible, especially to a teacher who has received an award in the form of a certification from the government for his dedication to the advancement of the world of education and learning. Even so, this does not rule out the possibility of an increase in the welfare of the teachers themselves. This is because all the aspects mentioned can affect the performance of teachers in carrying out their responsibilities and workload. Therefore, in this research will be carried out an analysis of the influence between each variable, either directly or indirectly. The results of the study show that: 1) The total scores of the Commitment (X1) and Welfare (Y) variables are in the high category, while the Certification (X2) and Performance (Z) variables are in the very high category; 2) Commitment (X1) and Certification (X2) variables have a direct effect of 52.02% and an indirect effect of 48% on Welfare (Y); 3) Commitment (X1) and Certification (X2) variables have a direct effect of 47.5% and an indirect effect of 52.5% on Performance (Z); 4) Welfare variable (Y) has a direct effect of 17.3% and another focus of 82.7% on performance (Z); and 5) Commitment (X1), Certification (X2), and Welfare (Y) variables have a total effect of 48.8% and another focus of 50.2% on Performance (Z).